Follicular changes in postpartum buffaloes (Bubalus bubalis) induced to cyclicity - LOHAN, I S; SAINI, M S; KAKER, M L; MALIK, R K; SINGH, B; GREWAL, S S (The Indian Journal of Animal Sciences, 2014)
Postpartum Murrah buffaloes (15) were studied in relation to ovarian follicular changes during induced oestrous cycle in summer and winter. Ovarian follicular dynamics were monitored daily up to 25 days post insemination through transrectal ultrasonography. Out of 15 animals 10 (66%) had 2 follicular wave patterns; 4 animals had 3 follicular waves (26%) and I animal had cystic ovaries. In 2 follicular wave patterns, the first follicular wave started between 1-2 days and follicle size reached maximum (9.7 Â± 0.6 mm) by day 6-7 and the second wave between 8-10 days with maximum follicle size between 18-19 days post induced estrus. In 3 follicular wave patterns, first wave began 1-2 days, follicle size reached maximum on 6-7 days; second wave started from 9-10 days, follicle size reached maximum on 15-16 days and third follicular wave between 16-17 days and maximum follicle size on 24-25 days post estrus. Six animals ovulated (40%) on the first day post estrus and 2 of these resulted in short span functioning corpus luteum and 3 (20%) ovulated later. Fewer number of medium and small size follicles were observed during the early part of the induced estrous cycle than the later part respectively. The ultrasonographic monitoring of 10 animals before (-3 days) induced-estrus showed the presence of dominant follicle, which culminated in ovulation.